Railway Bearing Prototypes Based on Plastic Waste HDPE and Nylon-Resin Fiber Epoxy - Tyas Damayanti, Ajeng; Muharjito, Muharjito; Prasetyo, Hanif (Journal of World Science, 2022)
Introduction: Material composite is ingredient congested when two or more materials, each with characteristics, are combined to make material new which nature more superior than component the main thing is in certain applications. Method: In this study, composite bearing specimens were made using the method compression molding with two variation composition that is HDPE 60% + fiber nylon 5% + epoxy 35% and composition HDPE 60% + 10% nylon fiber + 30% epoxy. This manufacturing method is done by inserting recycled HDPE, fiber, nylon, and epoxy resin into the mold. Next, the pressing process is carried out with a hydraulic press and heated at a temperature of 220°C using oven electricity. Results: Results testing material shows strong bending highest on variation composition HDPE 60% + fiber nylon 10% + Epoxy 30% that is as big as 17.21 MPa. Strength bending in this composition has increased from previous studies with a bending strength of 15.66 Mpa, but not yet. Fulfill standard bearing rail composite JIS E 1203:2007 as big as 17.5 MPa. Results testing pull with standard ASTM D638 obtained the highest tensile strength at 60% HDPE + 10% nylon fiber + 30% epoxy of 8.64 Mpa. Tensile strength on composition this experience enhancement from a previous study of 0.5041 MPa. Conclusion: Prototype bearing rail train fire composite made to a 1:4 scale of the original size, which refers to standard JIS E 1203:2007. Prototype bearing rail train fire conducted material testing using bending and tensile tests.